ROLE OF PORTUGUESE IN THE DEVELOPMENT OF PARATHAVAR COMMUNITY IN THOOTHUKUDI DISTRICT - G. Usha AND R. Malliga (MIRROR, 2018)
The entry of the Portuguese and the Dutch into the pearl fishery coast in the sixteenth and seventeenth centuries and their emphasis on pearl trade, especially in the international sphere, gave a new dimension to the socio-economic transactions of the Parava community. Their activities extended to the south- eastern coastal regions of Tamilnad and how their missionaries succeeded in converting large numbers of the fishermen (the ‘Paravar’) of the southern coast to Christianity. The Portuguese were the only European nation to be interested in the Indian trade. The Portuguese monopolised the European trade on South India. This paper provides detailed information about the role of Portuguese in the development of Parathavar Community in Thoothukudi district.